The Potential of Local Garlic (Allium sativum L.) to Become a Flavor Enhancer Through Lacto-Fermented Garlic - Firda Ainia Adha; Andrew Setiawan Rusdianto; Noer Novijanto; Maria Belgis (Proceeding of International Conference on Science, Health, And Technology, 2021)
Garlic is an agricultural commodity that is often used as an additional ingredient in various food that serve as a flavor enhancer. According to data from the Central Statistics Agency and the Directorate General of Horticulture of the Republic of Indonesia, in 2019 Indonesia's garlic production reached 88,816 tons. However, this amount is still not able to meet the demand for garlic in Indonesia which reaches 600,000 tons per year. To solve this problem, the Government of the Republic of Indonesia imports garlic from other countries. The problem of trade competition between local and imported garlic then arises. People prefer imported garlic because of the cheaper price and larger size. This condition causes farmers to not be able to survive in the competition and suffer losses. However, local garlic can actually compete in terms of quality. Local garlic has a sharper aroma with a more savory taste which will make the dish more delicious. Therefore, more attention to local garlic is needed, such as making innovations that can increase the value of local garlic. Lacto-fermented garlic is a food innovation that utilizes lactic acid bacteria (LAB) in the fermentation process. The fermentation process helps garlic produce a stronger aroma and taste as the allicin content increases. The fermentation process of garlic is carried out using the anaerobic fermentation method which lasts for 14 days. Garlic is fermented in a salt solution with 4 different concentrations consisting of 0%, 5%, 8%, and 10%. During the fermentation process, the aroma, garlic color, and solution color were observed. In terms of the aroma and color test aspects at the four concentrations used, the sample with a concentration of 8% on day 14 was selected as the best sample. This is because the osmosis process that occurs during fermentation is not excessive so that many organosulfur compounds in onions are still contained.